What do we learn from impurities and disorder in high-Tc cuprates? - Alloul, Henri (Frontiers in Physics, 2024)
We have performed a series of experimental studies that established that the differing morphologies of the phase diagrams versus hole doping n h of the various cuprate families are mostly controlled by defects and disorder. YBCO being among the minimally disordered cuprates we could introduce controlled defects allowing us to probe the metallic and superconducting states. We could demonstrate that the extent of the spin glass phase and the superconducting dome can be controlled by the concentration of spinless (Zn, Li) impurities substituted on the planar Cu sites. NMR frequency shift measurements establish that these defects induce in their vicinity a cloud with a Kondo like paramagnetic behavior. Its "Kondo" temperature and spatial extent differ markedly between the pseudogap and strange metal regimes. We have performed transport measurements on single crystals with a controlled content of in plane vacancies introduced by electron irradiation. At high T the inelastic scattering of the carriers has been found independent of disorder and completely governed by the excitations of the correlated electronic state. The low T upturns in the resistivity associated with single site Kondo like scattering are qualitatively in agreement with the local magnetism induced by spinless impurities. The apparent metal insulator crossover are only detected for very large defect content and